PENGEMBANGAN E-MODUL BERBANTUAN FLIPBOOK KEANEKARAGAMAN MANGROVE BERBASIS RISET DI TELAGA WASTI PADA MATA KULIAH KEANEKARAGAMAN TUMBUHAN - Nebore, Idola Dian Yoku; Anita, Agustina; Erari, Semuel Sander; Iwan, Iwan; Rumalolas, Nuryanti; Tuririday, Helena Trivona (FKIP Universitas Tanjungpura, 2025)
Students often face challenges in understanding botanical terms, which hinders their comprehension of plant diversity topics. Additionally, the lack of available e-modules has led students to rely heavily on internet sources, making the learning process less effective. This study aims to develop contextual e-modules focused on mangrove plants in Telaga Wasti as supplementary teaching materials for plant diversity courses. The research follows a Research and Development (R & D) approach, employing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to guide the creation of the e-modules. The research instruments consist of media and material expert validation sheets, student response questionnaire sheets, lecturer interview sheets, and pretest and posttest questions. The study evaluates the e-modules in terms of validity, practicality, and effectiveness. Validation by expert reviewers resulted in a score of 90,32%, categorized as